Libya - Mundy, Jacob (Hot spots in global politics, 2018)
Libya is teetering on the edge of collapse, having become a new safe haven for transnational terrorist organizations and the epicenter of the Mediterranean refugee crisis. This is the first book to document and explain the political, security, and humanitarian crises that have engulfed Libya -- Africa's largest oil exporting country -- since 2011.